Analysis of Switching Sequence Operation for Reduced Switch Multilevel Inverter With Various Pulse Width Modulation Methods - Kanike, Vinod Kumar; Raju, Saravanakumar (Frontiers in Energy Research, 2020)
Pulse Width Modulation (PWM) methods are used to control the switching sequence operations of conventional Multilevel Inverter (MLI) and Reduced Switch Multilevel Inverters (RSMLI). Many researchers proposed various RSMLIs with their switching sequence operation and PWM control techniques. But, the switching operations of RSMLIs are not similar to conventional MLIs which are major problem of switch control. Logical equations are proposed for the operation of RSMLIs with the multi carrier pulse width modulation methods like, Alternative Phase Opposition Disposition (APOD), Phase Opposition Disposition (POD) and Phase Disposition (PD). To operate the individual switch in RSMLI, logical operators are used to produce required pulse sequence from the sequence of PWM method and their analysis is not present in previous works. The proposed methodology and binary representation of PWM method are analyzed on various RSMLIs for 7 level output voltage. Control of individual switching sequence and the operation of RSMLIs are simulated using MATLAB/Simulink. THD comparison is presented for RSMLIs with various PWM methods.